Early proteinuria lowering by angiotensin-converting enzyme inhibition predicts renal survival in children with CKD - Belt, Sophie M. van den; Heerspink, Hiddo J. L.; Gracchi, Valentina; de Zeeuw, Dick; Wühl, Elke; Schaefer, Franz (Journal of the American Society of Nephrology, 2018)
Background Although pharmacotherapeutic proteinuria lowering was found to be nephroprotective in adults, the predictive value of early drug-induced proteinuria reduction for long-term renal survival in pediatric CKD is unknown. We analyzed data from the ESCAPE Trial for a potential association between initial antiproteinuric effect of standardized angiotensin-converting enzyme (ACE) inhibition and renal disease progression in children with CKD., Methods In total, 280 eligible children with CKD stages 2-4 (mean age 11.7 years old, median eGFR 46 ml/min per 1.73 m2, 71% congenital renal malformations) received a fixed dose of ramipril (6 mg/m2 per day) and were subsequently randomized to conventional or intensified BP control. We assessed initial proteinuria reduction from baseline to first measurement on ramipril (at 2.5±1.3 months). We used multivariable Cox modeling to estimate the association between initial proteinuria reduction and the risk of reaching a renal end point (50% eGFR decline or ESRD), which occurred in 80 patients during 5 years of observation., Results Ramipril therapy lowered proteinuria by a mean of 43.5% (95% confidence interval, 36.3% to 49.9%). Relative to proteinuria reduction <30%, 30%-60% and >60% reduction resulted in hazard ratios (95% confidence intervals) of 0.70 (0.40 to 1.22) and 0.42 (0.22 to 0.79), respectively. This association was independent of age, sex, CKD diagnosis, baseline eGFR, baseline proteinuria, initial BP, and concomitant BP reduction., Conclusions The early antiproteinuric effect of ACE inhibition is associated with long-term preservation of renal function in children with CKD. Proteinuria lowering should be considered an important target in the management of pediatric CKD.
Gesehen am 09.03.2020